BASSAMI Mohammed, ADRIAUCH Amine, BENKACEM Mariem, AZZIOUAZ Fatima, MIMOUNI Hicham, RKAIN Ilham (2024), Mandibular Mass Revealing Vesicular Thyroid Carcinoma A Case Report. International Journal of Innovative Science and Research Technology (IJISRT) IJISRT24MAY099, 188-192. DOI: 10.38124/ijisrt/IJISRT24MAY099. https://www.ijisrt.com/mandibular-mass-revealing-vesicular-thyroid-carcinoma-a-case-report - I. C. Oji; T. O. Ale; C. S. Odeyemi; O. I. Dare- Adeniran; O. A. Aliyu (International Journal of Innovative Science and Research Technology (IJISRT), 2024)
Fault is a regular incidence on distribution power system because distribution lines are always exposed to the environment with high probability of fault occurrence which when it happens, can cause hazardous conditions, equipment failures, power instability, huge financial loss and other forms of setback. In order to avoid these setbacks, it is necessary to detect and locate the fault on the network as fast as possible so as to prevent power system damages and reduce system downtime. This research study designed a smart fault location system model that detected and located ground faults at the point of occurrence using a developed 33 kV Ubulu-Uku radial distribution system as a test feeder and then formulated fault location equations which resulted into one single equation for all ground fault types on the network. The designed algorithm was evaluated on MATLAB 2023a environment using different line impedances of 0.01 Ω, 0.15 Ω, 0.35 Ω, 0.50 Ω, and 0.65 Ω which produced various ground faults located along path 6 section 17, path 8 secAtion 21, path 8 section 21, path 4 section 12 and path 8 section 21 with distance of fault from the main substation obtained at 3.51 km, 3.93 km, 4.03 km, 4.81 km, and 4.21 km. The results presented show performance of the designed algorithm and can be encouraged for practical implementation with promising result which will achieve some benefits like precise fault location information analysis, reduce the overall response time spent by maintenance crew to locate fault and reduce cost of operational maintenance and supply interruptions.